Pengaruh Ekonomi Value Added dan Market Value Added terhadap Return Saham - Rafky Aulya; Henri Agustin (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of Value Added Economy and Market Added Value on Stock Returns in Food and Beverage Companies. The population in this study are Food and Beverage Companies listed on the IDX for the 2016-2020 period. The research sample was determined by using purposive sampling method with a total sample of 37 Food and Beverage Companies. This study uses secondary data from the company's annual report. The analytical method used is panel data regression. The results showed that the economic value added variable had no effect on stock returns. The market value added variable has a significant effect on stock returns. The economic value added and market added value variables together have no effect on stock returns.